Tales from a NOT-SO fabulous life (Dork Diaries Series Book 1) - Rachel Renee Russell (London Simon & Schuster, 2010)
Nikki Maxwell has never been popular but, now she's started at a new school, she's hoping to leave her old dorky ways behind! Follow Nikki's adorkable life through sketches, doodles and diary entries as she spills all the details of her not-so-fabulous life full of BFF drama, hopeless crushes and an extremely cringe-worthy family!